Delayed diagnosis of proximal ureter injury after a blunt abdominal trauma in Korea: a case report - Soon Ki Min; Byungchul Yu; Gil Jae Lee; Min A Lee; Yang Bin Jeon; Youngeun Park; Kang Kook Choi; Hyuk Jun Yang (Journal of Trauma and Injury)
Traumatic ureteral injuries account for fewer than 1% of traumatic urologic injuries, and those caused by blunt trauma are even rarer than those caused by penetrating trauma. The symptoms associated with ureteral injury may be subtle, with or without hematuria, making it difficult to diagnose. We report the case of a 31-year-old man with a delayed diagnosis of proximal ureter injury after abdominal blunt trauma sustained in a motorcycle traffic accident. The patient underwent emergency laparotomy on admission for liver injury, mesenteric injury, and resultant hemoperitoneum. On postoperative day 6, he underwent angioembolization for suspected remnant intra-abdominal bleeding. Persistent symptoms of flank pain and leukocytosis led to follow-up imaging studies that revealed proximal ureter injury, and the patient underwent unilateral nephrectomy. This case stresses the importance of clinical suspicion for genitourinary injuries in the presence of abdominal trauma.